THE RELATIONSHIP AMONG EMOTIONAL EXHAUSTION, ORGANIZATIONAL CYNICISM, IN-ROLE PERFORMANCE, AND EMPLOYEE BADMOUTHING - Ronowati Tjandra; Wisnu Prajogo; Rahmat Purbandono; Ratna Puji Astuti (ITB AAS INDONESIA, 2023)
This research examines the relationship among emotional exhaustion, organizational cynicism, in-role performance, and employee badmouthing. The main idea of this research is testing the influence of emotional exhaustion on organizational cynicism, in-role performance, and employee badmouthing. Most research concerning emotional exhaustion focus of the influence of emotional exhaustion on employee performance and intention to leave. This research explores the influence of emotional exhaustion on organizational cynicism and employee badmouthing. 155 employees from various organizations participated in this research. This research has several findings. First, emotional exhaustion has positive influence on organizational cynicism. Second, emotional exhaustion has negative influence on in-role performance. Third, emotional exhaustion has positive influence on employee badmouthing. Fourth, organizational cynicism has positive influence on employee badmouthing. Fifth, in-role performance had negative influence on employee badmouthing.